Incidence of dry eye in post-operative cataract patient - Alka Ravi; Uma Shankar Singh; Archana Kumari; Pummy Roy (Kerala Journal of Ophthalmology)
Objective: To estimate the incidence of dry eye in post-operative patient undergoing cataract surgery. Materials and Methods: Schirmer’s test, tear break-up time (TBUT) test, and lissamine green staining of the cornea and conjunctiva for the evaluation of dry eye preoperatively and again at first and second follow-up examinations at 1 week and 1 month after cataract surgery were performed on 100 patients with senile cataract. Results: The patients were 61.25 years old on average, and 71 (71%) of them were men. According to the requirements of our study, none of the patients experienced dry eyes at the time of participation. Schirmer’s test results during the first and second follow-ups, respectively, varied from 12-35 mm and 8-24 mm postoperatively. At the first and second follow-ups, the mean TBUT was 13.12 ± 2.44 and 9.61 ± 2.22 seconds, respectively, whereas the lissamine green staining score was 3 in 66 (66%) and 1 in 62 (62%) patients, respectively. At the initial follow-up, grade 2 dry eye was discovered in 89% of the 56 patients who received phacoemulsification (p 0.001) and in 92% of the 66 patients who underwent small-incision cataract surgery (SICS) (p 0.001). At the second follow-up, 83% of patients who had SICS and 93% of those who had phacoemulsification had grade 0 dry eyes, respectively (p 0.001). Conclusion: The incidence of dry eye following cataract surgery was significant and largely unrelated to demographic and anthropometric characteristics, surgical technique, length of microscope exposure, and energy input. This dryness was only temporary in character and exhibited a downward trend, with a tendency to return to normal by the end of 1 month.